PENGARUH BOKASHI AMPAS TEBU DAN NPK ORGANIK PADA TANAMAN KUBIS (Brassica oleraceae Var. capitata) SECARA BERKELANJUTAN - Vira Pramita; Selvia Sutriana (UIR Press, 2022)
The purpose of this study was to examine the effect of interaction and the main effect of sugarcane bagasse and organic NPK in a sustainable manner. The research was conducted at the Experimental farm of the Faculty of Agriculture, Riau Islamic University, Pekanbaru during four months starting from October 2019 to January 2020. The design used in this study was a Factorial Completely Randomized Design (CRD), consisting of two factors (bagasse bokashi and organic NPK). The parameters observed were the number of leaves, the age at which the crop appeared, the age of harvest, the diameter of the crop, the fresh weight of the crop, and the fresh weight of the leaves. Data were analyzed statistically and the BNJ continued to test at the 5% level. The results of the research by interacting with bagasse and organic NPK significantly affected the parameters for the number of leaves, age of crop emergence, harvest age, and fresh weight of the crop. The best combination of bagasse bokashi at 270 g/plant and NPK Organic at 27 g/plant. The main effect of bagasse was significant on all parameters with the best treatment was a dose of 270 g/plant. The main effect of NPK organic was significant on all parameters with the best treatment was the dose of 27 g plant.